Risk communication: against the gods or against all odds?: problems and prospects of accounting for black swans - Wardman, Jaime; Mythen, Gabe (Taylor & Francis, 2016)
Recent academic and policy preoccupations with ‘Black Swans’ underscore the predicament of capturing and communicating risk events when information is absent, partial, incomplete or contingent. In this article we wish to articulate some key thematic and theoretical points of concurrence around which academic and practitioner interests in risk communication under conditions of ‘high uncertainty’ intersect. We outline the historical context and recent debate concerning the limits to ‘risk thinking’ spurred by Black Swans, and in particular how this calls for a more holistic approach to risk communication. In order to support a more critical foresight agenda, we suggest incorporating ‘adaptive governance’ principles to decenter focal risk communication concerns on the mitigation of short-term security threats, which critics argue can also lead to other unforeseen dangers. Finally, we welcome further interdisciplinary inquiry into the constitution and use of risk communication under high uncertainty.